Optimised handoff mechanism using RFID tags for a communication-based train control system. (28th November 2019) - Mohanasundaram, R.; Brindhadevi, Kathirvel; Sana, Arushi; Malhotra, Ankit
In a communication-based train control system, one of the most important aspects is ensuring that a mobile station is connected continuously to the zone controller to ensure continuous and precise transmission of the train's location, speed and other relevant information. Due to the continuous motion of the train handoffs between different APs is necessary to remain connected. This work aims to propose a location-based handoff method which will minimise handoff latency and provide better connections. The location-based handoff mechanism uses the concept of placing RFID tags at predetermined locations. Handoff is triggered at the location where the RFID tag is present and a connection is made to the new AP based on the channel information obtained. The architecture used in the scenario is a WiMAX architecture and connections are maintained with the help of routers contained within the mobile stations. The proposed handoff method provides better handoff latency and error free transmission in a system where precise information transmission is necessary.